Wiki Technology – Origin, Development and Importance - Stakić, Đorđe (Infotheca - Journal for Digital Humanities, 2024)
Late 20th century and early 21st century are marked by the emergence and expansion of Wiki technology in the field of informational technologies. The largest ever compiled encyclopedia, Wikipedia, emerged from Wiki technology. Compilation of Wikipedia as the most successful project based on Wiki technology showed true potential of Wiki software. This software is now widely used and imposes itself as a new standard. In addition to Wikipedia, local Wiki Web sites are important as well.